Thermally expandable fire-resistant composition, thermally expandable fire-resistant sheet and laminate

The thermally expandable fireproof composition, with styrenic elastomer and specific additives, addresses the issues of fire resistance and detachment by enhancing thermal expansion and maintaining insulation integrity.

JP7608302B2Active Publication Date: 2025-01-06FURUKAWA ELECTRIC CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021149762
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-14
Publication Date
2025-01-06
Estimated Expiration
2041-09-14

AI Technical Summary

Technical Problem

Existing fire-resistant compositions fail to maintain effective fire resistance and thermal expansion properties, and may detach from surfaces during a fire, compromising insulation.

Method used

A thermally expandable fireproof composition comprising styrenic elastomer, phosphorus-containing compound, polyhydric alcohol, foaming agent, inorganic filler, and inorganic reinforcing agent, with specific components like carbon black and titanium oxide, to enhance thermal expansion and fire resistance, preventing detachment.

Benefits of technology

The composition exhibits excellent thermal expansion and fire resistance, maintaining integrity on surfaces during a fire, ensuring effective insulation without detachment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608302000003
    Figure 0007608302000003
  • Figure 0007608302000004
    Figure 0007608302000004
  • Figure 0007608302000001
    Figure 0007608302000001
Patent Text Reader

Abstract

To provide a thermally expandable refractory composition that can achieve a thermally expandable refractory sheet having excellent thermal expandability in the event of a fire, also having excellent fire resistance, and less prone to peeling from a beam, a column and the like even when exposed to the heat of a fire, and a thermally expandable refractory sheet formed (constituted) using the thermally expandable refractory composition.SOLUTION: A thermally expandable refractory composition contains the following components (A)-(F): (A) a styrenic elastomer; (B) a phosphorus compound; (C) a polyhydric alcohol; (D) a foaming agent; (E) an inorganic filler; and (F) an inorganic reinforcing agent, the component (F) being at least one of carbon black and clay. There is also provided a thermally expandable refractory sheet constituted using the thermally expandable refractory composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally expandable fire-resistant composition, a thermally expandable fire-resistant sheet, and a laminate. [Background technology]

[0002] A fire-resistant (fire-preventing) composition or sheet containing a thermoplastic polymer is used to cover beams, columns, etc. of buildings to improve fire resistance (fire prevention). For example, Patent Document 1 describes an expandable fire-resistant composition containing (A) a thermoplastic resin, (B) a phosphorus compound, (C) a polyfunctional alcohol, (D) an inorganic fiber material, and (E) an inorganic filler. According to the technology described in Patent Document 1, the expandable fire-resistant composition forms a highly fire-resistant and heat-insulating carbonized (ashed) layer that expands and foams upon heating and / or flame, and is particularly excellent in fire resistance at high temperatures, and can easily be molded into a large-area sheet with high elasticity and strength. Furthermore, it is said to be capable of long-term use due to its excellent moisture resistance and water resistance. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-322374 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the inventors' studies have revealed that when a beam, a column, or the like covered with a sheet made of the foamable fireproof composition described in Patent Document 1 is heated by fire or the like, a part of the sheet may fall off (become missing), and the fire resistance (thermal insulation) may not be fully exhibited. Furthermore, the inventors' studies have revealed that the foamable fireproof composition requires further improvement in the fireproof properties of the composition itself, such as fire resistance and foamability (thermal expansion).

[0005] The present invention aims to provide a heat-expandable fire-resistant composition that can realize a heat-expandable fire-resistant sheet that has excellent thermal expansion during a fire, excellent fire resistance (thermal insulation), and is unlikely to fall off beams, columns, etc. even when exposed to the heat of a fire (a foam insulation structure that is unlikely to fall partially or entirely due to its own weight when heated), and a heat-expandable fire-resistant sheet formed (constructed) using the heat-expandable fire-resistant composition. [Means for solving the problem]

[0006] The above object of the present invention can be achieved by the following means. <1> Contains the following components (A) to (F): (A) Styrene-based elastomer (B) Phosphorus-containing compound (C) Polyhydric alcohol (D) Foaming agent (E) Inorganic filler (F) Inorganic reinforcement agent The thermally expandable fire-resistant composition, wherein said component (F) is at least one of carbon black and clay. <2> The component (E) is at least one of titanium oxide and silica. <1> The thermally expandable fire-resistant composition according to claim 1. <3> The thermally expandable fireproof composition contains 10 to 300 parts by mass of the component (E) relative to 100 parts by mass of the component (A). <1> or <2> The thermally expandable fire-resistant composition according to claim 1. <4> The component (F) contains carbon black. <1> ~ <3> 13. The thermally expandable fire-resistant composition according to claim 12 . <5> The component (F) satisfies at least one of the following conditions 1 and 2: <1> ~ <4> 2. The thermally expandable fire-resistant composition according to claim 1 . Condition 1: DBP oil absorption per 100 g of component (F) is 0 to 500 mL Condition 2: Average particle size 5~2000nm <6> The thermally expandable fireproof composition contains 0.01 to 200 parts by mass of the component (F) relative to 100 parts by mass of the component (A). <1> ~ <5> 13. The thermally expandable fire-resistant composition according to claim 12 . <7> <1> ~ <6> A heat-expandable fire-resistant sheet comprising the heat-expandable fire-resistant composition according to any one of claims 1 to 5. <8> <7> and at least one layer selected from a reinforcing material, an adhesive, and a release paper.

[0007] In the present invention, the term "composition" refers to a mixture in which two or more components are uniformly mixed. However, as long as the homogeneity is substantially maintained, some aggregation or uneven distribution may occur within the range in which the desired effect is achieved. Effect of the Invention

[0008] The heat-expandable fire-resistant composition and heat-expandable fire-resistant sheet of the present invention have excellent thermal expansion properties during a fire, excellent fire resistance (thermal insulation properties), and are unlikely to fall off from beams, pillars, etc. even when applied to beams, pillars, etc. and exposed to the heat of a fire. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a cross-sectional view of an H-shaped steel used in the test specimens produced in the examples and comparative examples of the present invention. [Diagram 2] 1 is a cross-sectional view of a test specimen prepared in an example of the present invention and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Thermally expandable fireproof composition> The thermally expandable fire-resistant composition of the present invention contains a styrene-based elastomer (component (A)), a phosphorus-containing compound (component (B)), a polyhydric alcohol (component (C)), a foaming agent (component (D)), an inorganic filler (component (E)), and an inorganic reinforcing agent (component (F)), wherein the component (F) is at least one of carbon black and clay. Hereinafter, the thermally expandable fire-resistant composition of the present invention may be simply referred to as the "composition of the present invention." The components contained in the composition of the present invention or components that may be contained therein may be used alone or in combination of two or more.

[0011] (styrene elastomer) The styrene-based elastomer (component (A)) is a thermoplastic elastomer having a soft segment and a hard segment derived from a styrene compound (a compound having a structure in which one substituted or unsubstituted vinyl group and one substituted or unsubstituted aromatic hydrocarbon ring (e.g., a benzene ring, a naphthalene ring, or an anthracene ring) are directly bonded to each other). Specific examples of styrene compounds include styrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 1,3-dimethylstyrene, α-methylstyrene, vinylnaphthalene, and vinylanthracene. Examples of the monomer that leads to the soft segment include a conjugated diene compound, and specific examples of the conjugated diene compound include butadiene (1,2-butadiene, 1,4-butadiene), isoprene, and 1,3-pentadiene. Specific examples of component (A) include styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (styrene-ethylene / butylene block copolymer, SEB), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (styrene-ethylene / butylene-styrene block copolymer, SEBS), styrene-isoprene block copolymer (SIR), hydrogenated styrene-isoprene block copolymer (styrene-ethylene / propylene block copolymer, SEP), styrene-isoprene-styrene block copolymer (SIS), hydrogenated styrene-isoprene-styrene block copolymer (styrene-ethylene / propylene-styrene block copolymer, SEPS), styrene-ethylene-isoprene block copolymer, hydrogenated styrene-ethylene-isoprene block copolymer, copolymers (styrene-ethylene-ethylene / propylene block copolymers), styrene-ethylene-isoprene-styrene block copolymers, hydrogenated styrene-ethylene-isoprene-styrene block copolymers (styrene-ethylene-ethylene / propylene-styrene block copolymers), (α-methylstyrene)-butadiene block copolymers, hydrogenated (α-methylstyrene)-butadiene block copolymers ((α-methylstyrene)-ethylene / butylene block copolymers), (α-methylstyrene)-butadiene-(α-methylstyrene) block copolymers, hydrogenated (α-methylstyrene)-butadiene-(α-methylstyrene) block copolymers ((α-methylstyrene)-ethylene / butylene-(α-methylstyrene) block copolymers), styrene-isobutylene block copolymers, and styrene-isobutylene-styrene block copolymers. From the viewpoints of ease of kneading the various components contained in the present invention and thermal expandability, it is preferable to select from at least one of styrene-butadiene block copolymer (SBR), hydrogenated styrene-butadiene block copolymer (styrene-ethylene / butylene block copolymer, SEB), styrene-butadiene-styrene block copolymer (SBS), hydrogenated styrene-butadiene-styrene block copolymer (styrene-ethylene / butylene-styrene block copolymer, SEBS), styrene-ethylene / propylene block copolymer, styrene-ethylene / propylene-styrene block copolymer, and styrene-ethylene-ethylene / propylene block copolymer, and hydrogenated styrene-butadiene-styrene block copolymer (styrene-ethylene / butylene-styrene block copolymer, SEBS) is the most preferable.

[0012] The physical properties of component (A) are determined under conditions of 150°C and a load of 21.2N according to the measurement method of ASTM D 1238 from the viewpoint of kneadability and ease of molding. The MFR (melt mass flow rate) value obtained under the above conditions is preferably 80g / 10min or less, more preferably 60g / 10min or less, and most preferably 40g / 10min or less. Meanwhile, it is practical for the MFR to be usually 1.0 / 10min or more. If the MFR obtained under the above conditions is less than 1 g / 10 min, the temperature is changed to 150° C. to 200° C. and the same measurement as above is carried out. If the MFR is 100 g / 10 min or more, the temperature is changed to 150° C. to 125° C. and the obtained value is used.

[0013] The composition of the present invention may contain a polymer other than component (A). The content ratio of component (A) in the polymer contained in the composition of the present invention is, for example, 80 mass% or more, may be 90 mass% or more, or may be 100 mass%. The polymer contained in the composition of the present invention is preferably composed of component (A). Examples of polymers other than component (A) include polyethylene resins, polypropylene resins, EVA (ethylene-vinyl acetate copolymer), fluororesins, methacrylic resins, epoxy resins, modified epoxy resins, silicone resins, urethane resins, vinyl chloride-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, and polyester-based thermoplastic elastomers.

[0014] (phosphorus-containing compounds) The phosphorus-containing compound (component (B)) used in the composition of the present invention is not particularly limited, and a wide variety of compounds generally used in thermally expandable fire-resistant compositions can be used. Specific examples of component (B) include red phosphorus, phosphate esters (e.g., triphenyl phosphate and tricresyl phosphate), metal phosphates (e.g., sodium phosphate and magnesium phosphate), ammonium phosphate, melamine phosphate, phosphoric amide, and ammonium polyphosphate compounds (e.g., ammonium polyphosphate, and melamine-modified ammonium polyphosphate). Of these, from the viewpoint of ensuring the presence of a sufficient amount of carbonized material in the foam insulation structure (in the foam insulation layer) produced by heating the composition of the present invention, and from the viewpoint of formability, shape retention, and long-term durability of the foam insulation structure formed by heating a heat-expandable fire-resistant sheet made from the composition of the present invention (hereinafter, the "heat-expandable fire-resistant sheet made from the composition of the present invention" may also be simply referred to as the "sheet of the present invention"), it is preferable that component (B) contains an ammonium polyphosphate compound. When the composition of the present invention is exposed to high heat such as fire and reaches the decomposition temperature of the ammonium polyphosphate compound, ammonia gas is generated from the ammonium polyphosphate compound, and phosphoric acid and condensed phosphoric acid are generated. The phosphoric acid and condensed phosphoric acid act as dehydration catalysts for organic substances such as polyhydric alcohols contained in the composition of the present invention, and the organic substances are carbonized, thereby generating carbonized substances in the foamed insulation structure. The content of component (B) in the composition of the present invention is not particularly limited, but from the viewpoint of suppressing the amount of carbonized material produced in the foamed thermal insulation structure and the generation of coarse bubbles in the foamed thermal insulation structure, the content is preferably 10 to 1,000 parts by mass, more preferably 20 to 500 parts by mass, and even more preferably 70 to 250 parts by mass, per 100 parts by mass of component (A).

[0015] (Polyhydric alcohol) The polyhydric alcohol (component (C)) used in the composition of the present invention is not particularly limited, and any of those generally used in thermally expandable fire-resistant compositions can be widely used. As described above, when the composition of the present invention is exposed to high heat such as fire, component (C) is carbonized. The decomposition temperature of component (C) is preferably 150° C. or higher, and more preferably 180° C. or higher. On the other hand, there is no particular upper limit to the decomposition temperature of component (C), but a temperature of 300° C. or lower is practical. Examples of component (C) include monopentaerythritol, dipentaerythritol, and tripentaerythritol, polysaccharides such as starch and cellulose, and oligosaccharides such as glucose and fructose, and at least one of these can be used. Among these, from the viewpoint of the thermal expansion of the composition of the present invention, it is preferable to use at least one selected from monopentaerythritol, dipentaerythritol, and tripentaerythritol. The content of component (C) in the composition of the present invention is not particularly limited, but from the viewpoints of skeleton formation of the foamed thermal insulation structure and shape retention of the foamed thermal insulation structure, the content is preferably 5 parts by mass or more and 200 parts by mass or less, more preferably 10 to 100 parts by mass, and even more preferably 25 to 80 parts by mass, per 100 parts by mass of component (A).

[0016] (foaming agent) The blowing agent (component (D)) used in the composition of the present invention may be any blowing agent commonly used in thermally expandable fire-resistant compositions. Specific examples of component (D) include melamine and its derivatives, dicyandiamide and its derivatives, azodicarbonamide, urea, and thiourea. Among these, melamine, dicyandiamide, azodicarbonamide, etc. are preferred because they have excellent efficiency in generating non-flammable gas, with melamine and dicyandiamide being more preferred, and dicyandiamide being most preferred. In the composition of the present invention, the content of component (D) is preferably 5 to 500 parts by mass, more preferably 30 to 200 parts by mass, and even more preferably 35 to 100 parts by mass, per 100 parts by mass of component (A), from the viewpoints of the thermal expandability of the composition and the fire resistance of the foamed insulation structure.

[0017] (Inorganic filler) Examples of the inorganic filler (component (E)) used in the composition of the present invention include silica, calcium carbonate, talc, diatomaceous earth, mica, kaolin, titanium oxide, zinc oxide, aluminum oxide, aluminum hydroxide, magnesium hydroxide, and bentonite, and at least one of these can be used. Among these, silica and titanium oxide are preferred, and titanium oxide is most preferred. Titanium oxide may be either rutile type or anatase type, but rutile type is more preferred. Component (E) has a high thermal decomposition temperature and therefore aids in the heat resistance effect of the carbonized material in the foam insulation structure. In the composition of the present invention, from the viewpoints of the thermal expandability of the composition, suppression of the generation of coarse bubbles in the foamed thermal insulation structure, and suppression of loss of the foamed thermal insulation structure, the content of component (E) is preferably 5 to 1,000 parts by mass, more preferably 10 to 300 parts by mass, even more preferably 50 to 200 parts by mass, and particularly preferably 70 to 150 parts by mass, per 100 parts by mass of component (A).

[0018] (Inorganic reinforcing agent) The inorganic reinforcing agent (component (F)) used in the composition of the present invention is at least one of carbon black and clay, and preferably contains carbon black. Specific examples of carbon black include porous carbon powder such as activated carbon, Ketjen black, channel black, furnace black, acetylene black, and graphite. and Graphite Fiber Maintenance Specific examples of clay include bentonite, mica, kaolin, and calcined kaolin. In the composition of the present invention, at least one of carbon black and clay contained in component (F) interacts with component (A) to form bound rubber. Since bound rubber has binding properties but a weak bonding force, the composition of the present invention has excellent thermal expansion properties, and the foamed insulation structure formed under high heat has excellent fire resistance (thermal insulation), and it is presumed that the loss of the foamed insulation structure can be effectively suppressed.

[0019] From the viewpoint of uniformity of the bubble diameter in the foamed insulation structure, the DBP oil absorption of component (F) is preferably in the range of 0 to 1000 mL per 100 g, and more preferably in the range of 0 to 500 mL. The DBP oil absorption (the amount of DBP (dibutyl phthalate) required to fill the voids between components (F)) is determined as follows. The DBP oil absorption is a value measured in accordance with JIS K 6217-4 (2008) and means the amount (mL) of dibutyl phthalate absorbed per 100 g of carbon black. From the viewpoint of preventing chipping of the foamed heat insulating structure, the average particle size (volume-based median size) of component (F) is preferably in the range of 1 to 10,000 nm, more preferably 5 to 2,000 nm.

[0020] In the composition of the present invention, from the viewpoints of the expandability of the composition, the suppression of the generation of coarse bubbles in the foamed thermal insulation structure, and the suppression of loss of the foamed thermal insulation structure, the content (total) of component (F) is preferably 0.01 to 1,000 parts by mass, more preferably 0.01 to 200 parts by mass, further preferably 1 to 100 parts by mass, and particularly preferably 5 to 50 parts by mass, per 100 parts by mass of component (A). Furthermore, when the composition of the present invention contains the below-described component (G), the content of component (F) is preferably 15 to 300 parts by mass, more preferably 30 to 200 parts by mass, and most preferably 50 to 150 parts by mass, per 100 parts by mass of component (G).

[0021] (Plasticizer) The composition of the present invention may contain a plasticizer (component (G)) to the extent that the effect of the present invention is not impaired. As component (G), a conventional plasticizer used in thermally expandable fire-resistant compositions can be used. Specific examples of component (G) include phthalate compounds such as di-2-ethylhexyl phthalate, diisononyl phthalate, and dibutyl phthalate; trimellitate compounds such as tri-n-trioctyl trimellitate, dipentaerythritol ester, and mixed alcohol trimellitate; fatty acid ester compounds such as butyl oleate; epoxy compounds such as epoxidized soybean oil, epoxidized linseed oil, and epoxidized fatty acid alkyl esters; adipic acid ester compounds such as isobutyl adipate and di-2-ethylhexyl adipate; phosphate compounds such as tricresyl phosphate, tri-2-ethylhexyl phosphate, triphenyl phosphate, 2-ethylhexyl diphenyl phosphate, and cresyl diphenyl phosphate; mineral oils such as aroma process oil and naphthene process oil; chlorinated products such as paraffin process oil, chlorinated paraffin, and chlorinated aliphatic esters; polymer oils such as polybutene and polybutadiene; and resins such as alkyd resins and xylene resins. At least one of these can be used. Of these, it is preferable to use a phthalate compound. In the composition of the present invention, the content of component (G) is preferably 200 parts by mass or less, more preferably 120 parts by mass or less, still more preferably 40 parts by mass or less, and particularly preferably 20 parts by mass or less, per 100 parts by mass of component (A), from the viewpoint of suppressing loss of the foamed insulation structure. When the composition of the present invention contains component (G), the content of component (G) is preferably 10 parts by mass or more, more preferably 5 parts by mass or more, per 100 parts by mass of component (A).

[0022] (Dispersant) The composition of the present invention may contain a dispersant (component (H)) to the extent that the effect of the present invention is not impaired. As component (H), a typical dispersant used in a thermally expandable fireproof composition can be used. As component (H), a fatty acid ester can be used. Specific examples of fatty acid esters include behenyl behenate, octyldodecyl behenate, stearyl stearate, glycerin monopalmitate, glycerin monostearate, glycerin monooleate, polyglycerin stearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, etc., and at least one of these can be used. Among these, glycerin monostearate is preferred. In the composition of the present invention, the content of component (H) is preferably 1 to 50 parts by mass, more preferably 3 to 40 parts by mass, and even more preferably 5 to 30 parts by mass, per 100 parts by mass of component (A), from the viewpoints of improving the dispersibility of the elastomer and additives and constructing a uniform foamed insulating structure.

[0023] (Other Ingredients) The composition of the present invention may contain components other than the above components (A) to (H) to the extent that the effects of the present invention are not impaired. Specific examples of components other than the above components (A) to (H) include pigments, fibers, wetting agents, lubricants, preservatives, antifungal agents, anti-algae agents, antibacterial agents, thickeners, leveling agents, antifoaming agents, crosslinking agents, UV absorbers, antioxidants, and catalysts, and at least one of these may be used. In the composition of the present invention, the total content of components other than the above components (A) to (H) can be, for example, 10 parts by mass or less, preferably 8 parts by mass or less, and also preferably 5 parts by mass or less, per 100 parts by mass of component (A).

[0024] <Method for preparing thermally expandable fire-resistant composition> The composition of the present invention can be prepared by kneading at least components (A) to (F). Kneading can be performed by mixing the above components using various kneading machines (e.g., kneader, Banbury mixer, mixing roll). Kneading may be performed while heating the mixture of each component as necessary. For example, when using component (A) in the form of beads or pellets, the components other than component (A) can be added and kneaded while heating the mixture to the softening (melting) temperature of component (A) or higher using a heating device.

[0025] <Thermal expansion fireproof sheet> The sheet of the present invention is obtained by forming the composition of the present invention into a sheet shape. The thickness of the sheet of the present invention may be appropriately set according to the purpose of use, and may be, for example, 0.01 to 100 mm. The thickness of the sheet of the present invention is preferably 0.1 to 30 mm, and more preferably 0.5 to 20 mm.

[0026] <Manufacturing method of thermally expandable fireproof sheet> The sheet of the present invention can be produced by molding in a conventional manner except for using the composition of the present invention. Examples of the molding method include a method of pouring the composition of the present invention into a mold and removing it after drying, a method of applying the composition of the present invention to release paper using a heating coater and then winding it up, a method of processing the composition of the present invention into a sheet using an extrusion molding machine, a method of feeding the composition of the present invention between a pair of rolls and processing it into a sheet, a method of pelletizing the composition of the present invention and then processing it into a sheet using an extrusion molding machine, a method of rolling the composition of the present invention into a sheet using a calendar consisting of multiple heated rolls, etc. The molding temperature is preferably higher than the softening temperature of component (A), and molding is usually performed at 80 to 120°C.

[0027] The sheet of the present invention may have a laminated structure with a reinforcing material, an adhesive (including a pressure sensitive adhesive), a release paper, etc., within the scope of not impairing the effects of the present invention. Examples of the reinforcing material that can be used include woven fabric, nonwoven fabric, mesh, metal mesh, aluminum sheet, glass fiber sheet, aluminum glass fiber sheet, etc. The reinforcing material can have a laminated structure of one or more reinforcing materials. The reinforcing material can also be incorporated between the thermally expandable fireproof sheets. As the adhesive, ordinary adhesives and pressure sensitive adhesives used for thermally expandable fire resistant sheets can be used. A release liner is usually laminated over the adhesive and is used to protect the adhesive.

[0028] The sheet of the present invention can be used as a material for covering various substrates such as buildings. Examples of the parts where the substrate is used include walls, pillars, floors, beams, roofs, and stairs. Examples of materials constituting the substrate include metals, concrete, wood members, and resin members. These substrates may be appropriately subjected to surface treatment, rust prevention treatment, and the like. Furthermore, the sheet of the present invention can be applied to structures other than buildings, including automobile components, electronic parts, electrical appliances, pipelines, and other products and parts that require fire resistance (fire prevention).

[0029] When adhering the sheet of the present invention to a substrate, various methods are possible, such as a method in which an adhesive is applied to the substrate in advance and then the substrate is adhered, a method in which a covering material having an adhesive layer is adhered to the substrate, or a method in which the covering material is fixed to the substrate with nails, tacks, etc.

[0030] When the sheet of the present invention is applied to a substrate, it is preferable to treat the substrate so that the substrate is entirely covered. In the present invention, a single layer is possible, but two or more sheets of the sheet of the present invention may be laminated and applied to the substrate.

[0031] The butt portions of the sheets of the present invention can be treated by overlapping the sheets of the present invention, overlapping narrow sheets or tapes, filling with putty, or the like. EXAMPLES

[0032] The present invention will be described in more detail with reference to the following examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the present invention should not be interpreted as being limited to the following examples except as specified in the present invention.

[0033] Example 1 A thermally expandable fire-resistant composition was prepared by the following procedure using the components shown in Table 1 in the amounts shown in Table 1 below, and the thermally expandable fire-resistant composition was molded to obtain a thermally expandable fire-resistant sheet. The styrene-based elastomer was kneaded in a kneader at 100°C for 5 minutes to melt the styrene-based elastomer. Pentaerythritol, dicyandiamide, ammonium polyphosphate, glycerin monostearate, titanium oxide, and carbon black were added to the molten styrene-based elastomer. These components were kneaded in a kneader at 100°C for 15 minutes to obtain a heat-expandable fire-resistant composition. The heat-expandable fire-resistant composition immediately after kneading was rolled by a calendar roll consisting of multiple heat rolls to process it into a sheet shape, thereby producing a heat-expandable fire-resistant sheet with a length of 670 mm, a width of 300 mm, and a thickness of 2 mm. The obtained heat-expandable fire-resistant sheet was laminated with an aluminum glass cloth with a length of 670 mm, a width of 300 mm, and a thickness of 0.138 mm to obtain a heat-expandable fire-resistant laminate sheet of Example 1.

[0034] (Examples 2 to 16 and Comparative Examples 1 to 13) In the preparation of the heat-expandable fire-resistant composition of Example 1 and the production of the heat-expandable fire-resistant laminate sheet, the heat-expandable fire-resistant compositions and heat-expandable fire-resistant laminate sheets of Examples 2 to 16 and Comparative Examples 1 to 13 were obtained in the same manner as in the preparation of the heat-expandable fire-resistant composition of Example 1 and the production of the heat-expandable fire-resistant laminate sheet, except that the compositions of Examples 2 to 16 and Comparative Examples 1 to 13 shown in Table 1 below were used instead of the composition of the heat-expandable fire-resistant composition of Example 1.

[0035] (Fire resistance) A test specimen having the cross section shown in Figure 2 was prepared using the H-beam (10) shown in Figure 1. Note that the drawings themselves are all schematic explanatory drawings and do not directly represent the actual size or positional relationship. The material of the H-beam (10) complies with SS400 (JIS G 3101 (2015)), and the sizes of the H-beam are t1 = 250 mm, t2 = 125 mm, t3 = 6 mm, and t4 = 9 mm, which comply with JIS G 3192 (2014). In the test specimen, an H-steel (10) combined with an ALC (lightweight aerated concrete cured under high temperature and high pressure steam) plate (1) was covered (sealed) with a heat-expandable fire-resistant laminated sheet (aluminum glass cloth (2) and heat-expandable fire-resistant sheet (3) composed of a composition) of the examples and comparative examples. This test specimen was set in the heating furnace of the test equipment (Towa Fireproofing Industry Co., Ltd. small fireproofing test equipment). The test specimen was heated for one hour from the thermocouple (4) (Fukuden Co., Ltd. K-CCBF 1P*1 / 1.0 4,000L hot junction / M4Y terminal (product name)) side in accordance with the standard heating curve of ISO834, raising the temperature in the heating furnace to approximately 945°C, and the temperature measured by the thermocouple was evaluated according to the following evaluation criteria. "Good" and "Good" indicate passing the test. The results are shown in Table 1 below. -Evaluation criteria- ○: 550℃ or less △: Over 550 and below 700℃ ×: Over 700℃

[0036] (Thermal expansion) The heated test specimen was left in the test device until it reached room temperature (50°C), after which the thickness of the foamed insulation laminate remaining on the H-beam was measured and the value calculated using the following formula 1) was applied to the following evaluation criteria for evaluation. "Good" and "Good" indicate passing the test. The results are shown in Table 1 below. Formula 1) Thickness of foam insulation laminate structure produced by heating / Thickness of thermally expandable fireproof laminate sheet before heating "The thickness of the foamed heat insulating structure formed by heating" means "the thickness of the heat-expandable fire-resistant laminate sheet after heating." The "thickness of the foamed heat insulating structure formed by heating" was determined as follows. After the test, for the foam insulation laminated structure remaining on the surface of the H-beam indicated by t2 (Figure 1), the maximum value (1 point) and minimum value (1 point) of the total thickness of the foam insulation structure and the glass cloth are divided by 2 to calculate the thickness. -Evaluation criteria- ○: 15 or more △: More than 5 and less than 15 ×: Less than 5

[0037] (Whether or not there is any loss in the foam insulation structure) After the thermal expansion evaluation was performed as described above, the test specimen and the test equipment were observed to check whether the foam insulation structure had fallen off (missed) from the H-shaped steel, and the results were evaluated according to the following evaluation criteria. "Good" and "Good" indicate passing the test. The results are shown in Table 1 below. -Evaluation criteria- ◯: The foam insulation structure did not fall off at all (nothing was missing). △: Part of the foam insulation structure had fallen off (some parts were missing, but more than half remained). ×: Most (more than half) of the foam insulation structure fell off.

[0038] [Table 1]

[0039] [Table 2]

[0040] Example: Comparison:

[0041] (Thermoplastic elastomer) Styrene-based elastomer (Aron Chemical Industries, Ltd.: AR-710N (product name), styrene-ethylene / butylene-styrene block copolymer, MFR 5 g / min (ASDM D 1238, 150°C, 21.2 N) (component (A)) Polyamide elastomer (Arkema: PEBAX5533 (trade name), polyamide-polyether copolymer) Vinyl chloride elastomer (Mitsubishi Chemical Corporation: Sunprene F8807-1 (product name)) Non-crosslinked olefin elastomer (JSR Corporation: 1601B (product name)) Polyester elastomer (Aronkasei Co., Ltd.: ES-A50NX (product name))

[0042] (thermoplastic resin) EMA (Ethylene-Ethyl Acrylate Copolymer) (Japan Polyethylene Co., Ltd.: EB050S (product name)) Saponified ethylene vinyl acetate copolymer (Tosoh Corporation: H-6051K (product name))

[0043] (Plasticizer (Component (G)))

[0044] Phthalate ester (manufactured by Kyoei Chemical Co., Ltd.: DINP (product name))

[0045] (Polyhydric alcohol (component (C))) Pentaerythritol (Taisei Kayaku Co., Ltd.: NeuRizer P (product name))

[0046] (Foaming agent (component (D))) Dicyandiamide (Mitsubishi Chemical Corporation: DICY15 (product name))

[0047] (Phosphorus-containing compound (component (B))) Ammonium polyphosphate (manufactured by Hangzhou Jiasi Fire Retardant Chemical Co., Ltd.: AP102 (product name))

[0048] (Dispersant (Component (H))) Glycerin monostearate (Rikemal S-100 (product name))

[0049] (Inorganic filler (component (E))) Titanium oxide (Sakai Chemical Industry Co., Ltd.: R-11P (product name)) (Average particle size 200nm) Silica (Shin-Etsu Chemical Co., Ltd.: QSG-30 (product name)) (Average particle size 30nm) Calcium carbonate (Shiraishi Calcium Co., Ltd.: Hakuenka CC (product name), average particle size 40 nm) Magnesium hydroxide (manufactured by Konoshima Chemical Co., Ltd.: Magseeds X (product name), average particle size 1000 nm) Magnesium oxide (Konoshima Chemical Co., Ltd.: PSF-150 (product name), average particle size 600 nm) Talc (Nippon Talc Co., Ltd.: Nano Ace D-600 (product name), average particle size 600 nm) Glass fiber (manufactured by Nittobo: SS 10-420 (product name), average cut length 0.3 mm)

[0050] (Inorganic reinforcing agent (component (F))) Carbon black (Asahi Carbon Co., Ltd.: #70 (product name)) (DBP oil absorption 101mL / 100g, average particle size 28nm) Clay (Sanyo Clay Industry Co., Ltd.: TP Clay (commercial product), average particle size 4000 nm)

[0051] The following can be seen from Table 1: The laminates of Comparative Examples 1 to 6, which were made using a thermoplastic elastomer or thermoplastic resin other than the component (A) specified in the present invention, failed in fire resistance. The laminates of Comparative Examples 1 to 5 also failed in thermal expansion, and the laminates of Comparative Examples 3 to 6 lost most of the foam insulation structure. The components defined in the present invention ( F In the laminates of Comparative Examples 7 to 9, 12 and 13 produced without using the foam insulating structure, most of the foam insulating structure was lost. The laminates of Comparative Examples 9, 12 and 13 also failed the fire resistance and thermal expansion properties. The components defined in the present invention ( F ) was used. Comparative ExampleLaminates Nos. 10 and 11 failed the fire resistance test, and the laminate of Comparative Example 10 also failed the thermal expansion test. In contrast, the laminates of the present invention in Examples 1 to 16 were excellent in fire resistance and thermal expansion properties, and even if there was any loss of the foam insulation structure, it was only partial. [Explanation of symbols]

[0052] 1. ALC (high-temperature, high-pressure steam-cured lightweight aerated concrete) board 2 Aluminum glass cloth 3. Thermally expandable fireproof sheet made of the composition 4 Thermocouples 10H steel

Claims

1. Contains the following components (A) to (F): (A) Styrene-based elastomer (B) Phosphorus-containing compound (C) Polyhydric alcohol (D) Foaming Agent (E) Inorganic filler (F) Inorganic reinforcing agent the component (B) is selected from red phosphorus, phosphate esters, metal phosphates, ammonium phosphates, melamine phosphates, amide phosphates, and ammonium polyphosphate compounds; said component (E) does not contain carbon black or clay; The component (F) is at least one of carbon black and clay, and satisfies at least one of the following conditions 1 and 2: Condition 1: DBP oil absorption per 100 g of component (F) is 0 to 500 mL Condition 2: Average particle size 5 to 2000 nm A thermally expandable fireproof composition comprising, relative to 100 parts by mass of the component (A), 20 to 500 parts by mass of the component (B), 25 to 80 parts by mass of the component (C), 30 to 200 parts by mass of the component (D), 10 to 300 parts by mass of the component (E), and 5 to 100 parts by mass of the component (F). (However, this does not include a thermally expandable fireproof composition in which the surface distance of the dispersed phase is 0.1 μm or more, and a thermally expandable fireproof composition containing thermally expandable graphite.)

2. 2. The thermally expandable refractory composition of claim 1, wherein said component (E) is at least one of titanium oxide and silica.

3. 3. The thermally expandable fire-resistant composition of claim 1 or 2, wherein said component (F) comprises carbon black.

4. A heat-expandable fire-resistant sheet comprising the heat-expandable fire-resistant composition according to any one of claims 1 to 3.

5. A laminate comprising a layer of the thermally expandable fireproof sheet according to claim 4 and at least one layer selected from a reinforcing material, an adhesive, and a release paper.

Citation Information

Patent Citations

  • Foaming type fireproof composition having water resistance

    JP2002294078A

  • Foamable fire-retardant composition excellent in fire resistance

    JP2002322374A

  • Rubber composition and foamed molded item using the rubber composition

    JP2005206648A

  • Fire resistive material for joint and its manufacturing method, earthquake resisting slit material making use of the fire resistive material for joint and its manufacturing method and building structure equipped with the earthquake resisting slit material

    JP2006045950A

  • Foaming type fireproof composition

    JP2006249364A